Analyzing Feshbach resonances: a 6Li-133Cs case study - Pires, Rico; Repp, Marc; Ulmanis, Juris; Kuhnle, Eva; Weidemüller, Matthias (Physical review. A, Atomic, molecular, and optical physics, 2014)
We provide a comprehensive comparison of a coupled channel calculation, the asymptotic bound-state model (ABM), and the multichannel quantum defect theory (MQDT). Quantitative results for 6Li−133Csare presented and compared to previously measured 6Li−133CsFeshbach resonances (FRs) [Repp et al., Phys. Rev. A 87, 010701(R) (2013)]. We demonstrate how the accuracy of the ABM can be stepwise improved by including magnetic dipole-dipole interactions and coupling to a nondominant virtual state. We present a MQDT calculation, where magnetic dipole-dipole and second-order spin-orbit interactions are included. A frame transformation formalism is introduced, which allows the assignment of measured FRs with only three parameters. All three models achieve a total rms error of <1G on the observed FRs. We critically compare the different models in view of the accuracy for the description of FRs and the required input parameters for the calculations.
Im Titelzusatz sind die Zahlen 6 und 133 hochgestellt
Gesehen am 29.07.2020